(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
This text analyzes the situation of abortion in Mexico in the light of the judgment Acción de Inconstitucionalidad 148/2017, with which the Supreme Court of Justice of the Nation declared the unconstitutionality of the provision of the Coahuila’s Penal Code, according to which the voluntary interruption of pregnancy, apart from specific conditions, was a crime. This is a leading case, first of all because this is the very first time in which the discussion on the constitutionality of the prison sentence for women who decide to terminate their pregnancy voluntarily has been carried out from a gender perspective. Secondly, the ruling adopts an inclusive perspective that recognizes the right to decide for women and other people with gestational capacity (such as trans men, non-binary people, and other identities). Finally, the judgment recognizes the constitutional guarantee of women’s right to decide on their life plan linked to motherhood.